CTA Project Completion Report: Monitoring, Evaluation and Impact Assessment - Khadar, Ibrahim; Aniambossou, Imelda; Leguit, Josina (Technical Centre for Agricultural and Rural Cooperation, 2020)
Management of a monitoring and evaluation (M&E) system is a critical function in international development institutions such as CTA. CTA’s goals for investing in a strong M&E system are to promote accountability, learning, decision-making and visibility.